HALAL TOURISM AS A PROCESSING STRATEGY BIL HAL PERSPECTIVE ADINUGRAHA - Rifani Raniasati (UIN Walisongo Semarang, 2023)
The method of da'wah is a way or path that is carried out by a da'i to make it easier for him to achieve the goal of da'wah. Da'wah bil-hal is all matters relating to basic human needs, especially those concerning material and physical needs, so that dakwah bil-hal matters more on the advancement of people's lives and livelihoods in an effort to improve living standards in accordance with Islamic principles. Implementing the halal concept in the tourism sector has become a trend and is needed by Muslim and non-Muslim countries. Seeing the increasing prospects for halal tourism, researchers want to see that the concept of halal tourism also has the integration of da'wah values that can be taken and applied and not only take advantage economically. So the purpose of this study is to analyze halal tourism as a bil-hal da'wah strategy through the adinugraha perspective. This research is a qualitative research with the type of library research. Source of data comes from primary and secondary data. Primary data comes from journals and books from adinugraha. While secondary data comes from other sources of literature that are relevant to this research.